The Russian-Mongolian vector of the eastern energy strategy of Russia: role of energy potential of the Baikal region - Saneev Boris; Ivanova Irina; Izbuldin Alexander; Muzychuk Svetlana; Maysyuk Elena; Borisov Gennady; Butkhuyag Sodovin (E3S Web of Conferences, 2018)
The paper is concerned with the specific features of Russia’s economic development in a new economic environment that caused the need to revise the priorities of energy policy. The research presents the initial conditions, targets and strategic directions of energy development in the East of the country. The focus is made on the priority lines of innovation and technology cooperation between Russia and Northeast Asian countries in the field of energy, and recommendations on necessary conditions and initiatives for their successful implementation are given.